Goodnight moon (Baby's first books, ,, 1997)
In this classic of children's literature, beloved by generations of readers and listeners, the quiet poetry of the words and the gentle, lulling illustrations combine to make a perfect book for the end of the day. In a great green room, tucked away in bed, is a little bunny. "Goodnight room, goodnight moon." And to all the familiar things in the softly lit room--to the picture of the three little bears sitting on chairs, to the clocks and his socks, to the mittens and the kittens, to everything one by one--the little bunny says goodnight. One of the most beloved books of all time, Goodnight Moon is a must for every bookshelf. This board book edition is the right size for little hands and is the perfect gift for baby showers, toddler birthday parties, and holidays.

Kaleidoscope (Thorndike Press youth large print middle reader, ,, 2022)
An astounding new feat of storytelling from Brian Selznick, the award-winning creator of The Invention of Hugo Cabret and Wonderstruck . A ship. A garden. A library. A key. In Kaleidoscope , the incomparable Brian Selznick presents the story of two people bound to each other through time and space, memory and dreams. At the center of their relationship is a mystery about the nature of grief and love which will look different to each reader. Kaleidoscope is a feat of storytelling that illuminates how even the wildest tales can help us in the hardest times.